Place Affect Interventions During and After the COVID-19 Pandemic - Ramkissoon, Haywantee (Frontiers in Psychology, 2021)
The COVID-19 health and economic crisis has also brought a rise in people being unable to cope with their existing medical conditions and other issues including domestic violence, drugs, alcohol among others. Suicidal tendencies have been on the rise (Gunnell et al., 2020; Pfefferbaum & North, 2020; McIntyre, & Lee, 2020, Sher, 2020). Feelings of isolation causing emotional distress in place confined settings has put additional pressure on the healthcare systems demanding that we find additional and complementary means of support for those in need (Ramkissoon, 2020a). This is important not only in the current pandemic, but also in a post pandemic world. The goal is to collectively contribute and address the recurring calls for actions to maintain global wellbeing and public health. An important discussion to bring on the table is the need to promote interventions for people to cope with the pandemic and to adjust to the post-pandemic world. Promoting affective attitudes towards place can foster wellbeing outcomes (Ramkissoon, Mavondo, & Uysal, 2018; Townsend et al., 2018). This has important benefits and is of relevance to governments, policy-makers and healthcare professionals in delivering better health care equipping people with coping mechanisms both throughout the pandemic and in the long-run. The key challenge however is how to foster these place affect attitudes meeting the changing demands in a post pandemic world. It is in the middle of a crisis that the conversation needs to start about how to strategically plan for the recovery.